The Effect of Compensation and Career Development on Employee Turnover Intention in the Culinary Sector - Yadewani, Dorris; Reni Wijaya (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2021)
This study aims to determine whether there is an effect of compensation and career development on employee turnover intention either simultaneously or partially. Based on the type of data and analysis, this research is classified as causal associative research. The research method used is descriptive quantitative. The population of this research is all employees of PT Setya Kuliner Mandiri dBesto Chicken And Burger. Method of collecting datadone through a questionnaire. The data analysis method uses SPSS 24. The results of this study prove thatthere is an effect of giving and career development on employee turnover intention, either simultaneously or partially.